The First Results of the Evaluation of Long-Term Nicorandil Treatment Effect on the Probability of Cardiovascular Complications in Patients with Stable Coronary Artery Disease (Data of Observational NIKEA Study) - S. Yu. Martsevich; Yu. V. Lukina; N. P. Kutishenko; V. P. Voronina; N. A. Dmitrieva; A. V. Zagrebelnyy; O. V. Lerman; O. V. Gaisenok; T. A. Gomova; A. V. Ezhov; A. D. Kuimov; R. A. Libis; et al. (Рациональная фармакотерапия в кардиологии)
Aim. To assess the influence of addition of nicorandil on long-term cardiovascular complications in patients with chronic coronary artery disease (CAD) in the framework of a prospective observational study.Material and methods. Prospective observational multicenter NIKEA study included 590 patients with stable CAD. All patients were recommended to add nicorandil to their baseline therapy. After 21 months, 547 telephone contacts were made, the life status of 524 people was specified, 23 patients were lost to follow-up. The following complications were registered: death from any cause; non-fatal myocardial infarction (MI); non-fatal stroke; urgent myocardial revascularization; hospitalization due to deterioration of CAD, chronic heart failure (CHF) or atrial fibrillation (AF). In 479 patients, a telephone survey was performed to identify adherence (persistence) to nicorandil– i.e. to verify the continuing the treatment for the prescribed duration.Results. During the follow-up period, 15 deaths were recorded, the causes of which were as follows: 3 CAD (2 MI, 1 left ventricular aneurysm), 1 pulmonary embolism, 2 CHF; 1 stroke, 1 oncology, 1 bilateral pneumonia. In the remaining 6 cases, the causes of death were not known. Cardiovascular (CV) complications were MI (8 cases in 7 patients, 1 patient had 2 MI in the follow-up period, 3 patients from this group died), stroke in 6 patients (7 cases, 1 patient had 2 strokes, 1 patient died). Urgent percutaneous coronary intervention was performed in 3 patients (in 2 patients due to acute MI, in 1 patient due to unstable angina). During the observation period, 21 people were urgently hospitalized due to deterioration of clinical condition. According to the results of a medical survey, by the end of the follow-up period, 237 people were not adherent to prescribed nicorandil, and 242 patients took the recommended medication (adherent patients). The main cardiovascular complications and death from any cause (р<0.001) as well as the number of urgent hospitalizations (р=0.017) were significantly more common in non-adherent to nicorandil patients in comparison with adherent patients.Conclusion. The overall rate of CAD complications in NIKEA study was typical for patients with stable CAD receiving contemporary medical therapy. Addition of nicorandil significantly reduced the rate of CV complications in adherent patients in comparison with non-adherent patients.